Symphysio-Fundal Height Measurement as a Means of Gestational Age Assessment in the Second Half of Pregnancy at the University of Ilorin Teaching Hospital, Nigeria (Nepal Journal of Obstetrics and Gynaecology, 2012)
Aims: Accurate determination of gestational age (GA) is an important part of obstetric care. The aim of this study is to determine the reliability of Symphsio-Fundal Height (SFH) measurement in assessing Gestational Age in the second half of pregnancy. Methods: A total of 390 pregnant Nigerian women carrying uncomplicated singleton pregnancies between the gestational age of 20-40 weeks had SFH measurements done at the antenatal clinic, and ultrasonic biparietal diameter (BPD) and femur length (FL) determination at the fetal assessment unit, maternity wing of the University of Ilorin Teaching Hospital, Ilorin, Nigeria. The patients were followed up subsequently and managed till delivery. At delivery each baby was examined within the first 48 hours of life and gestational age at birth was assigned using the Ballard method. Results: Of the 390 patients studied, SFH correctly assessed GA in 80% compared to 81.3% for BPD (P = 0.43), 82.1% for FL (P – 0.41), 84.1% for BPD and FL (p = 0.35. There is no significant difference in the sensitivity of SFH 93.1% and ultrasound 97.9%. There is also no significant difference in the margin of error between the true gestational ages obtained by the two methods (SFH 15-41days Vs ultrasound 15-33days). Combined ultrasound parameters(BP & FL),FL, BPD and SFH were progressively less closely correlated with the Ballard age of the fetus.Conclusions: This study showed that accurate measurement of the SFH is a reliable method of gestational age assessment in the second half of pregnancy.NJOG 2011 Nov-Dec; 6 (2): 27-32 DOI: http://dx.doi.org/10.3126/njog.v6i2.6753